2004
DOI: 10.1021/es049473m
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Role of Heat Activation in Enhancing Serpentine Carbon Sequestration Reactions

Abstract: As compared with other candidate carbon sequestration technologies, mineral carbonation offers the unique advantage of permanent disposal via geologically stable and environmentally benign carbonates. The primary challenge is the development of an economically viable process. Enhancing feedstock carbonation reactivity is key. Heat activation dramatically enhances aqueous serpentine carbonation reactivity. Although the present process is too expensive to implement, the materials characteristics and mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 14 publications
6
94
2
Order By: Relevance
“…The majority of previous research has focused on the aqueous carbonation of naturally occurring silicate minerals such as serpentine (Mckelvy et al, 2004;Alexander et al, 2007;Krevor and Lackner, 2011), olivine (Haug et al, 2010), limestone (Symonds et al, 2009) and wollastonite (Tai et al, 2006;Huijgen et al, 2006c;Daval et al, 2009) due to their high calcium or magnesium content. Although the CO 2 storage capacity of these natural Ca-Mg-silicate minerals is sufficient to fix the CO 2 emitted from the combustion of fossil fuels, the technological carbonation of these minerals is slow and energy demanding.…”
Section: Alkaline Wastes As Adsorbentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of previous research has focused on the aqueous carbonation of naturally occurring silicate minerals such as serpentine (Mckelvy et al, 2004;Alexander et al, 2007;Krevor and Lackner, 2011), olivine (Haug et al, 2010), limestone (Symonds et al, 2009) and wollastonite (Tai et al, 2006;Huijgen et al, 2006c;Daval et al, 2009) due to their high calcium or magnesium content. Although the CO 2 storage capacity of these natural Ca-Mg-silicate minerals is sufficient to fix the CO 2 emitted from the combustion of fossil fuels, the technological carbonation of these minerals is slow and energy demanding.…”
Section: Alkaline Wastes As Adsorbentsmentioning
confidence: 99%
“…Various studies have addressed methods to speed up the kinetics of direct aqueous carbonation including physical and chemical pretreatment (Maroto-Valer et al, 2005a, b), electrolysis and heat pretreatment , and mechanical activation methods (McKelvy et al, 2004;Park and Fan, 2004;Haug et al, 2010;Haug et al, 2011). O'Connor et al (2002) investigated approaches to reduce particle size, and increase surface area, and elevate process temperature and pressure by thermal treatment or steam activation.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The stable products of the dehydroxylation reaction of pure magnesian lizardite under hydrothermal conditions are talc, forsterite, and water (O'Hanley et al 1989). Various authors (e.g., McKelvy et al 2004;Brindley and Zussman 1957) reported low-angle peaks in X-ray diffractograms of thermally treated serpentine phases, indicating that amorphization is not complete and that dehydroxylation produces intermediate partially ordered structures. Although differing in detail, early studies by Ball and Taylor (1963) and Brindley and Hayami (1965) proposed reaction sequences with disordered dehydroxylated intermediates.…”
Section: Dehydroxylation Products: a Talc-like Intermediate And Forstmentioning
confidence: 99%
“…Elevated temperature and pressure using finely powdered silicate minerals accelerate carbonation reactions rates (Maroto-Valer et al, 2005;McKelvy et al, 2004), but the costs are high limiting industrial application. A large fraction of the estimated costs is associated with grinding of the silicate minerals to smaller particles (> 60 % of the total costs) (Gerdemann et al, 2007;Huijgen et al, 2007;Renforth et al, 2011).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%